Co-designed neck exercise (EPIC-Neck) vs usual exercise care for people with chronic non-specific neck pain: protocol for a randomised feasibility study with process evaluation - Jonathan Price; Alison Rushton; Natalie Ives; Kate Jolly; Priti Parmar; Colin Greaves (Pilot and Feasibility Studies)
Abstract Background Clinical guidelines recommend that people with chronic non-specific neck pain self-manage symptoms with physiotherapy-led exercise. However, current exercise strategies have modest short-term effects, engagement is poor, and 48% of people continue to experience long-term and recurrent pain. Updated exercise strategies co-produced using complex intervention development frameworks are required that consider the behavioural, psychological, environmental, and technical aspects of exercise prescription and patient adherence to optimise symptom outcomes, long-term engagement, and self-management. This study tests the feasibility and acceptability of the EPIC-Neck programme (“Exercise Prescription Improved through Co-design”) which is grounded in evidence and theory and was co-produced using intervention mapping principles. The aim of the EPIC-Neck programme is to optimise the short-term outcomes of and long-term engagement with neck exercise. Methods This is a randomised feasibility study with process evaluation to assess the feasibility and acceptability of the EPIC-Neck programme and inform the design of a large-scale definitive trial evaluating the clinical and cost-effectiveness of the EPIC-Neck programme. A multicentre two-arm randomised controlled feasibility study aiming to recruit 45 adults with chronic non-specific neck pain will be conducted in UK NHS musculoskeletal physiotherapy departments. Recruitment will be from waiting lists and clinic advertisements. Participants will be individually randomised in 2:1 ratio to either the EPIC-Neck programme (n = 30) or usual exercise care (n = 15). The primary feasibility objective is to determine whether to continue to a large-scale definitive trial by evaluating delivery fidelity, acceptability, contamination, and rates of recruitment and retention (outcome completion at follow-up). Other feasibility objectives are to evaluate safety, define usual exercise care, refine the EPIC-Neck programme and training, and explore the demographics of people who do and do not enrol onto the study. Outcomes will be assessed by questionnaires at baseline and at 3- and 6-month post-randomisation, appointment audio-recordings, and one-to-one semi-structured interviews with participants receiving the EPIC-Neck programme (n = 12–15) and physiotherapists. Discussion This feasibility study will provide evidence of the feasibility and acceptability of the EPIC-Neck programme and guide the development of a definitive randomised controlled trial evaluating its clinical and cost-effectiveness within the NHS. Trial registrations ISRCTN81746901.